Method and apparatus for laser processing of silicon by filamentation of burst ultrafast laser pulses - HOSSEINI, S. ABBAS (2015)
A method for laser processing of Silicon includes placing a Kerr material into engagement with the Silicon forming an interface therebetween. A laser beam is applied having at least one subpulse in a burst envelope operating at a first wavelength. The laser beam passes through a distributive lens focusing assembly and to the Kerr material. The first wavelength is modified to a plurality of second wavelengths, some of which are effective for processing Silicon. Photoacoustic compression processing is produced by the laser pulse energy by a portion of second wavelengths delivered through the interface and to the Silicon which initiates Kerr Effect self-focusing which is propagated in the Silicon by additional energy input to the Silicon thus producing a filament within the Silicon.